Comparison of Optimal Solutions of Clusters Created Using Clustering Algorithm with Meta-Heuristic Algorithms in Capacity Vehicle Routing Problem - Sehitoglu, Adem; Aghayeva, Charkaz (Institute of Electrical and Electronics Engineers Inc., 2023)
Vehicle Routing Problem (VRP) has been recognized as an important segment in logistics transportation. Selection of suitable vehicle routes plays a crucial role in improving the economic benefits of logistics operations. The Capacity Vehicle Routing Problem (CVRP) is one of the most popular routing problems. At CVRP, a fleet of capable vehicles located in a central warehouse is used to deliver products to a range of geographically dispersed customers with known demand. The routing problem discussed in this study will be examined in two stages. First, k subsets will be created with the k-means algorithm for a customer set consisting of N numbers. In the second stage, each of the clusters created will be compared in terms of distance and time, and the solution performances obtained by the Ant Colony, Tabu Search and Simulated Annealing algorithm. © 2023 IEEE.
5th International Conference on Problems of Cybernetics and Informatics, PCI 2023 -- 28 August 2023 through 30 August 2023 -- Baku -- 195003
Keywords: k-means algorithm; Meta-Heuristic Algorithm; Optimization; Vehicle Routing Problem